Encouraging women's labor force participation in transition countries - Norberto Pignatti (IZA World of Labor, 2016)
Increasing women's labor force participation is important to sustainable economic development, especially in economies with highly educated women and an aging population. Women's participation varies across transition countries, driven by such economic and social factors as traditional views of gender roles and limited government support for caregivers. Still, in all countries there is clear scope for policies aimed at increasing women's participation. In particular, in countries where women's educational attainment is already high, policies to support a better work-life balance and female entrepreneurship look particularly promising.
Keywords: J13; J16; J21; J22; P23; P52; 330; female labor force participation; transition countries; aging; work-life balance; female entrepreneurship